The not-so-barren ranges - Scott, Kim (2016)
© Thesis Eleven Pty, Ltd., SAGE Publications. This is an impressionistic and informal essay written near the end of a novelist's Australia Research Council funded research project: 'Developing narratives from language and stories indigenous to the south coast of Western Australia', and informed by how that research project morphed into an emphasis on revitalization of Noongar language, and the attempt to restore connections between a particular Creation Story and landscape in an area regarded as 'massacre territory'. A sympathetic reader might think of the topic as 'The Wirlomin Noongar Language and Stories Project meets The Barren Ranges'.